Sistem Informasi Manajemen Penjualan Pada UMKM Menggunakan Codeigniter (Studi Kasus : UMKM Cie Cie Koeraw) - Salima, Ade; Afriansyah, Riki; Josi, Ahmat (Jurnal Inovasi Teknologi Terapan, 2023)
Cie-Cie Koeraw is an UMKM engaged in the culinary field, namely the sale of brittle products in the Bangka Belitung Islands Province. This UMKM have difficulty competing with other businesses that have used e-commerce in marketing. For this reason, it is necessary to develop a sales management system for this UMKM with an emphasis on sales and management features to be able to manage buying and selling transactions and reporting. The development method used to develop the intended system is the Rapid Application Development (RAD) method. This method consists of 4 phases, namely planning, design, construction, and testing. The testing was carried out using the blackbox testing method which concluded that the system could run properly. In addition, user acceptance testing was also carried out by producing a satisfaction percentage of 82,83% for the ease of use of the system, 82,67% for the benefits of using the system, and 84,67% for the suitability of the system with user requests.